CCDA self-study designing for cisco internetwork solutions (Desgn) - Teare, Diane (Cisco Press, 2004)
CCDA Self-Study: Designing for Cisco Internetwork Solutions (DESGN) is a fully updated and revised edition of Designing Cisco Networks. This title offers comprehensive, foundation learning on designing small routed and switched networks. As an early-stage exam preparation tool, the book provides detailed coverage of all CCDA 640-861 exam objectives. This title presents a broad range of network design principles and guidelines. Readers learn about the Enterprise Composite Network Model and how it simplifies the complexity of modern network design. The book teaches readers how to design campus networks in a hierarchical, modular fashion, design WAN networks, develop an IP network addressing scheme, and select optimal routing protocols for various designs. Readers also learn how to assess security solutions and the implications of voice traffic over a data network. A running case study puts readers in the role of a network administrator tasked with proposing solutions to common design problems. Chapter-ending review questions reinforce chapter topics, and job aids support real-world applications.